Echtzeit. Die Kunst der Langsamkeit : Real Time. The Art of Slowness. - Adolphs, Volker; Berg, Stephan; Ohrtmann, Baptist; Winkler, Wolfgang (Köln : Wienand Verlag, 2016)
Alÿs, Francis ; Bergmann, Benjamin ; Claerbout, David ; Dreher, Peter ; Formanek, Mark ; Hendricks, Jochem ; Honert, Martin ; Hulten, Sofia ; On, Kawara ; Kitzinger, Thomas ; Krause, Jürgen ; Kwade, Alicja ; Manders, Mark ; Marclay, Christian ; Martin, Kris ; Müller, Horst ; Nauman, Bruce ; Opalka, Roman ; Popova, Yelena ; Pousttchi, Bettina ; Risch, Jens ; Schmidt, Jan ; Signer, Roman ; Sugimoto, Hiroshi ; Uriarte, Ignacio ; Vautier, Ben ; Van Warmerdam, Marijke ; Wesely, Michael ; Zaugg, Remy
Tentoonstelling ' Echtzeit - Die Kunst der Langsamkeit / Real Time - The Art of Slowness', Kunstmuseum Bonn, 09.06.2016 - 04.09.2016.
Duits
Engels
boek